A new marker sequence for systematics of medically important fungi based on amino acid sequence of the largest subunit of RNA polymerase I. (2nd November 2016) - Yamanishi, Chiaki; Alshahni, Mohamed Mahdi; Sano, Ayako; Nakamura, Ikuo; Makimura, Koichi
Abstract: Molecular evolution has dominated taxonomic studies for decades, replacing traditional methods for identification and classification. However, there is a need for better markers to resolve the problems that have limited their usefulness. In this report, we introduce the protein tag (Ptag) sequence, a highly polymorphic amino acid sequence within the C-terminal region of the largest subunit of RNA polymerase I, as a new systematic tag sequence for delineating the evolutionary history of medically important fungi. As Ptag sequences are highly polymorphic between species and low within species, 42 fungal species representing the main taxonomic groups in the phyla Ascomycota and Basidiomycota were tested. The phylogenetic tree inferred from the Ptag sequences showed high consistency with the accepted classification of the Assembling the Fungal Tree of Life (AFTOL) project. Moreover, it could resolve the interspecies phylogenetic relationships of the tested taxa. In contrast, the phylogeny inferred from the nucleotide tag (Ntag) sequence, encoding the Ptag peptide, displayed lesser discriminatory power in resolving the phylogenetic relationships among distantly related taxa. In the case of closely related fungal species, the phylogenetic trees for Ptag and Ntag sequences were consistent with the tree for ITS1 sequences of 11 dermatophytic species. Taken together, the Ptag sequences should contribute to inferring phylogeny among species whereas the Ntag sequences should be useful to analyze variations among closely related species to resolve taxonomic issues in fungi.